The Effect of Good Reasoning in the Poetry of Ibn Sahl Al-Ishbili Al-Andalusi, 649 AH - Al-Gharbawi, Israa Abdel Reda (Journal of Tikrit University for Humanities, 2024)
Effective reasoning is a mode of refinement in communication and a technique of persuasive speech as it stimulates the reader’s imagination and provokes their conscience. It accomplishes this by presenting a humorous and fictitious justification for accepting an unfamiliar subject. Hence, the examination of sound logical thinking in Ibn Sahl’s poetry aimed to uncover the creative elements within these texts by emphasizing the artistic impact of rhetorical art in its integration with poetic texts, employing suggestive language and exquisite imagery, and scrutinizing the poetic structures that emerged in Ibn Sahl’s poetry. To demonstrate the rhetorical significance of this vibrant hue and the appropriateness of the fictitious rationale for its intended goal. We addressed the examination of the subject matter by dividing it into two sections: an introduction and a conclusion. The introduction encompasses an exploration of the notion of sound reasoning, the rationale behind its selection, as well as the study technique and strategy.